Attitudes Concerning Sexual Behavior towards Risky Sexual Behavior of Sexual Transmitted Infections among Male Adolescents in Indonesia - Helda, Helda; Muchlisa, Nurul (UI Scholars Hub, 2021)
There has been an increase of sexually transmitted infections (STIs) such as HIV/AIDS worldwide, especially in Indonesia. Several studies on adolescent behavior, especially the male as the main predictor, reported increased in STIs’ cases due to risky sexual behavior. This study aimed to show the relationship between attitudes, sexual behavior, and the risks of STIs among male adolescents in Indonesia based on the Indonesia Demographic and Health Survey (IDHS) data in 2017. This cross-sectional study involved 10,547 male adolescents using the total sampling method according to the inclusion and exclusion criteria. Data were analyzed using a complex sample logistic regression test. This study was found that the proportion of risky sexual behavior of STIs was10% of which 29.8% agreeable attitude male adolescents. Agreeable attitude male adolescents were found able to improve the risk of engaging in risky sexual behaviors of STIs (p-value = 0.018; prevalence odd ratio (POR) = 1.135). The male adolescents who had an agreeable attitude towards sexual behavior could improve the risk of having risky sexual behavior of STIs 1,135 times; however, the attitude variable was not necessarily a major risk factor for the risky sexual behavior of STIs. Knowledge and education were not related to the risky sexual behavior of STIs.